If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -1p) = 4 Reorder the terms: (-1p + x) = 4 Remove parenthesis around (-1p + x) -1p + x = 4 Solving -1p + x = 4 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1x' to each side of the equation. -1p + x + -1x = 4 + -1x Combine like terms: x + -1x = 0 -1p + 0 = 4 + -1x -1p = 4 + -1x Divide each side by '-1'. p = -4 + x Simplifying p = -4 + x
| 6a+5b=12c | | 3(t+6)-16=-7 | | 39.30=6s+3.48 | | z+3.1=12.1 | | 5+3(1+2(2x-3))+1=2x-3 | | -3y+x=10 | | 9n-20n+9n+10=-10 | | (-4)+7.1= | | 2x^3+5x^2-8x-7=0 | | 5x-2(3-x)=-(4+x) | | -4r+4+6r=16 | | x-4=40+5x | | 3n-4=2n-1 | | t=8x | | (5x^2-4x-12)=0 | | 6x-4x=3x+2 | | 5s+3.03=37.58 | | 8(x+3x)=9+12x | | 7v+2=13 | | (-5.3)-(-7.8)= | | 5-3(7-5x)=4(x+2)-46 | | y+4y=12 | | 10k=-9k-6 | | (4x+12)+(8x-2)= | | 5+4h=9+2h | | 0=4x^3+8x^2-28x-56 | | 6xm=1 | | 8(x+3x)=12x+9 | | -2+b-2=10 | | x+80=2x+30 | | 3(2x+5)=14x+8-8x+7 | | -5x-2=26+2x |